2018
DOI: 10.3917/spub.180.0141
|View full text |Cite
|
Sign up to set email alerts
|

Motivations des agents obstétricaux qui décident d’exercer en milieu rural au Niger

Abstract: This study highlighted the complexity of individual motivation, which depends on a multitude of factors and is expressed differently according to individual trajectories. Improving access to public health service status, and a position of responsibility providing support to health personnel by district managers through positive and formative supervision could be initiatives to support the retention of health personnel in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…As in high- and middle-income countries, in low-income countries where health workers shortages in rural and remote areas hamper access to care, studies have shown a positive correlation between rural origin, rural exposure and the students’ likelihood of opting for rural practice [2530]. In a survey among medical and nursing students from nine African and Asia countries, Silvestri et al found that a long duration in a rural setting was likely to anticipate selecting a rural practice [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in high- and middle-income countries, in low-income countries where health workers shortages in rural and remote areas hamper access to care, studies have shown a positive correlation between rural origin, rural exposure and the students’ likelihood of opting for rural practice [2530]. In a survey among medical and nursing students from nine African and Asia countries, Silvestri et al found that a long duration in a rural setting was likely to anticipate selecting a rural practice [25].…”
Section: Introductionmentioning
confidence: 99%
“…Uganda’s experience of community-based education for undergraduate health professions students’ resulted in an increased proportion of students who expressed intentions to practice in rural areas [29]. In Niger, a study on the motivations of obstetric healthcare personnel to work in rural areas suggests that rural origin may be a motivator for health workers to accept rural posting [30].…”
Section: Introductionmentioning
confidence: 99%